Bridging the incentive-cost gap: incentivizing sustainable crop residue management to address burning practices - Deepak Varshney; Ramsha Khan; Banerjee, Anurag; Chakraborty, Shreya; Kiran Kumara, T.M.; Nain, J.S. (TAFSSA, 2024)
Crop residue burning (CRB) remains a major challenge in India, particularly in Punjab, Haryana, and Uttar Pradesh, contributing significantly to environmental, public health, and economic issues. The primary reason for stubble burning is its low cost compared to alternative crop residue management (CRM) methods. Efforts to mitigate CRB include policy interventions and management measures, especially in Haryana, focusing on costs, incentives, and farmers’ preferences. The adoption of CRM practices is shaped by financial viability, incentive availability, and socio-economic factors. A comprehensive approach that addresses these factors is essential to promote sustainable CRM adoption and reduce the adverse impacts of stubble burning.